INHERITANCE LAW OF GRANDCHILDREN IN ISLAMIC MAJORITY COUNTRIES AND ANALYSIS OF ARTICLE 185 OF KHI IN INDONESIA - Dazriani, Wa Dazriani (Jurnal Hukum Khaira Ummah, 2023)
Muslim jurists agree to impose Islamic law on the life of Muslims. The fundamental issue in Islamic law is the question of the development of modern life which is followed by new legal problems which require an answer to it by using Islamic law. The field of inheritance law has experienced a very significant development, caused by the increasingly complex needs of society and its thinking can change in accordance with the times. Among them are Islamic inheritance law is developing with the existence of surrogate heirs, whose application in Indonesia is regulated by Compilation of Islamic Law (KHI). The objection to the sound of Article 185 KHI about the successor heir is still very often debated and considered vulnerable to multiple interpretations even by the judges in Religious Courts. The word "can" allows for "ijtihad" or judge's judicial independence when it comes to deciding cases. In connection with this, the question arises, how the law of inheritance of grandchildren in Muslim majority countries and how the analysis of Article 185 KHI in Indonesia? Furthermore, it will be studied by using library method, that is by collecting library data and primary data that will support this research.Keywords: Inheritance Law, Substitute Heir